Bronchial sleeve anastomosis in children: a single-center experience demonstrating safety and efficacy - Da, Min; Wang, Tao; Wang, Yang; Yu, Jiexin; Xu, Yang; Mo, Xuming; Qi, Jirong (Frontiers in Pediatrics, 2026)
ObjectiveTo evaluate the technical feasibility, safety, and clinical outcomes of bronchial sleeve anastomosis in a pediatric case series encompassing two main etiologies (trauma and tumor).MethodsA retrospective analysis was conducted on 8 pediatric patients who underwent bronchial sleeve resection at our center between May 2018 and May 2025. Preoperative diagnosis was confirmed by computed tomography, magnetic resonance imaging, and bronchoscopy. Collected data included demographic characteristics, surgical parameters, pathological results, perioperative outcomes, and follow-up information.ResultsAll eight procedures were successfully completed without perioperative mortality. The mean operative time was 306.88 ± 127.31 min, with mean intraoperative blood loss of 51.25 ± 23.57 mL. The mean duration of mechanical ventilation was 16.06 ± 12.57 h, chest tube drainage was maintained for 234.86 ± 91.04 h, and the mean postoperative hospital stay was 25.00 ± 8.45 days. The median follow-up period was 2.7 years (range: 0.6–7.1 years). Perioperative complications included two cases of mild anastomotic stenosis, both successfully managed with bronchoscopic cryotherapy, and one case of chylothorax that resolved with conservative drainage. The trauma group required significantly longer postoperative mechanical ventilation compared to the tumor group (P < 0.05). At the last follow-up, all patients were alive with patent airways, recovered pulmonary function, and had resumed normal activities. No tumor recurrence was observed in the oncology patients.ConclusionBronchial sleeve resection represents a safe, feasible, and effective lung-preserving procedure in carefully selected pediatric patients. This technique allows complete lesion removal while maximizing pulmonary function preservation and promoting long-term quality of life, establishing it as a preferred surgical option for children with severe airway trauma or bronchial tumors.